Flyway structure, breeding, migration and wintering distributions of the globally threatened Swan Goose Anser cygnoides in East Asia - Damba, Iderbat; Fang, Lei; Yi, Kunpeng; Zhang, Junjian; Batbayar, Nyambayar; You, Jianying; Moon, Oun-Kyong; Jin, Seon-Deok; Liu, Bo Feng; Liu, Guanhua; Xu, Wenbin; Hu, Binhua; et al. (Wildfowl, 2020)
Telemetry data, wintering waterbird surveys and expert knowledge are used here to describe the links between the summer and winter distributions of the Swan Goose Anser cygnoides in East Asia, and to determine the status of the species. Updated information suggests the existence of at least two discrete migratory flyways in the region: an â€œInland flywayâ€ and a â€œCoastal flywayâ€. The Inland flyway consists of birds that summer in Mongolia, the Durian steppe and northeast China, extending east to Khanka Lake in far eastern Russia. These geese winter in the Yangtze River floodplain in China, congregating at Poyang and Shengjin Lakes. Total wintering numbers for this group of birds were estimated at c. 54,400 in recent years, a decline from c. 78,000 in the early 2000s. Birds of the Coastal flyway seem discrete from those following the Inland flyway and occur further east, spending the summer at Udyl Lake and northern Sakhalin Island in Far East Russia. They migrate to winter mainly on the Minjiang River estuary (Fujian Province, China), with a few remaining to winter in South Korea. About 400 Swan Geese have been counted in the Coastal flyway population in recent years, and, following declines from 800 in the early 2000s, it is thought that they currently face extinction. Our results highlight that urgent and effective conservation efforts are needed to protect this declining population of a globally threatened species, especially those wintering in Korea and the Minjiang Estuary. New data provide a scientific basis for the conservation of this species in the region, but also highlight the need for improved monitoring and management of the declining numbers wintering in China.